Online Learning (Online) for Elementary School Students During the Covid-19 Pandemic - Lubis, Syibrina Jihan (Cattleya Darmaya Fortuna, 2022)
The Covid-19 pandemic has disrupted the conventional learning process. Since the COVID-19 pandemic, education systems across the country have switched to online learning systems, especially at the elementary school (SD) level. This study aims to analyze the online learning process, the supporting factors and the inhibiting factors for teachers in carrying out online learning during the Covid-19 pandemic. This research was conducted at SDS Bunga Tanjong Morawa. This research uses descriptive qualitative research with case study method. The subjects used in this study were elementary school teachers at SDS Bunga Tanjong. Data collection techniques used in this study were interviews and documentation. The result of this research is that the Covid-19 pandemic has had a very big impact on the learning process, learning that is usually carried out in person is now being shifted to online learning. Students feel bored and bored while carrying out learning. Online learning conducted for elementary school age children is considered less effective. There are several factors that support teachers in the online learning process, namely the availability of mobile phones, quotas and a stable internet network. In addition to the factors that support online learning, there are also several inhibiting factors for teachers in online learning. The inhibiting factors include not all students have cellphones and there are still many parents who are busy working. There are several factors that support teachers in the online learning process, namely the availability of mobile phones, quotas and a stable internet network. In addition to the factors that support online learning, there are also several inhibiting factors for teachers in online learning